CRACINA, potier et décorateur lézovien méconnu - Richard Delage; Jean-Marc Séguier (Revue Archéologique du Centre de la France)
One of the terra sigillata moulded bowls found at Saint-Sauveur-lès-Bray (Seine-et-Marne), “Port aux pierres”, bears a stamp with the name CRACINA. This potter was working at Lezoux (Puy-de-Dôme) and up to now is known as a potter who makes wheel-thrown pots. The discovery of this vessel and others, which has remained unpublished until now, reveals a new aspect of his work as a decorator linked to BANVVS I.